2008
DOI: 10.1016/j.cub.2008.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal Visual Input for Odor Tracking during Fly Flight

Abstract: Flies generate robust and high-performance olfactory and visual behaviors. Adult fruit flies can distinguish small differences in odor concentration across antennae separated by less than 1 mm [1], and a single olfactory sensory neuron is sufficient for near-normal gradient tracking in larvae [2]. During flight a male housefly chasing a female executes a corrective turn within 40 ms after a course deviation by its target [3]. The challenges imposed by flying apparently benefit from the tight integration of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 37 publications
5
67
0
Order By: Relevance
“…1). Under normal flight conditions, flies depend upon visual feedback to localize the source of an odor during flight (Frye et al, 2003), which they use to maintain flight heading in a plume (Duistermars and Frye, 2008). Here we demonstrate an olfaction-dependent increase in the gain of yaw optomotor transformations and a decrease in the gain of sideslip transformations (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…1). Under normal flight conditions, flies depend upon visual feedback to localize the source of an odor during flight (Frye et al, 2003), which they use to maintain flight heading in a plume (Duistermars and Frye, 2008). Here we demonstrate an olfaction-dependent increase in the gain of yaw optomotor transformations and a decrease in the gain of sideslip transformations (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Closed-loop experiments with this method are more challenging but might alter the response dynamics by putting the fly in an alternative behavioral state. Finally, our experimental conditions were designed specifically to isolate optomotor responses from other important sensory inputs such as mechanosensory feedback from the halteres and odor signals from the antennae, which strongly influence the dynamics of wing-beat-mediated equilibrium responses (Sherman and Dickinson, 2004;Duistermars and Frye, 2008). During free flight these additional inputs certainly interact with the visual dynamical wing beat response.…”
Section: Impulse Response Estimates For Optomotor Behaviormentioning
confidence: 99%
“…The combination of reduced saccadic reorientations and spatial gradient evaluation biases overall flight orientation towards either the plume (steering 'up' the gradient) or the anti-plume (steering 'down' the gradient). This demonstrates that the animal actively tracks the local minimum of aversive BA intensity in a manner qualitatively identical to tracking the local maximum of attractive vinegar intensity (Duistermars and Frye, 2008a;Duistermars et al, 2009). There was no difference between the mean plume acquisition time or probability in the presence of an attractive or aversive stimulus (Fig.3C,D), further evidence that flies are as adept at locating and orienting away from an aversive odor source as orienting towards an attractive odor source, even at low concentrations of BA.…”
Section: Flies Use the Same Sensorimotor Transformations To Dynamicalmentioning
confidence: 74%
“…visual conditions) similarly impacts active tracking of an attractive and aversive odorant (Fig.5). Previous work from our laboratory and others has demonstrated that flies integrate visual and olfactory stimuli to track appetitive odor plumes in flight (Chow and Frye, 2008;Frye and Duistermars, 2009;Chow et al, 2011;Krishnan et al, 2011), and that saccade amplitude and frequency represent independent control parameters (Wolf and Heisenberg, 1990;Tammero and Dickinson, 2002;Bender and Dickinson, 2006), which are themselves influenced by odor (Duistermars and Frye, 2008a). …”
Section: Flies Use the Same Sensorimotor Transformations To Dynamicalmentioning
confidence: 96%
See 1 more Smart Citation